A Preliminary Study on Developing ESP-Based Teaching Materials for Intercultural Business Communication Classes - Baetty Baetty; Difiani Apriyanti; Silvia Djonnaidi; Kotrini Kotrini (Politeknik Negeri Padang, 2023)
This research was conducted to investigate students' basic knowledge of intercultural communication aimingat gettingsome insight for improving the teaching materials and teaching delivery for the Intercultural Business CommunicationsubjectinPoliteknik Negeri Padang. It is a small-scale study on students' perception of cultural sensitivity in communicating withpeoplefromdifferent international language backgrounds for work purposes. Both close-ended and open-ended questionnaires were designedtoinvestigate to what extent intercultural communication aspects need to be introduced into the syllabus of the targetedsubject. Theresults of this study indicated that students did not fully understand the concept of appropriateness in communicating across culturesin a broader context, and their knowledge of related cultural issues in the international communication context for workneedstobeimproved. The conclusion generated from this research is that even though cross-cultural elements need to be introducedtoteachingEnglish in vocational higher education, careful planning is required to avoid a cultural clash with the local Minangkabauwisdom.This study recommends implementing the 'global Englishes' approach in introducing western cultural values in professional andbusiness interaction in designing lesson plans and teaching materials